2023
DOI: 10.1093/jhered/esad001
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of genomic diversity within North American squamates

Abstract: Comparisons of intraspecific genetic diversity across species can reveal the roles of geography, ecology, and life history in shaping biodiversity. The wide availability of mitochondrial DNA (mtDNA) sequences in open-access databases makes this marker practical for conducting analyses across several species in a common framework, but patterns may not be representative of overall species diversity. Here, we gather new and existing mtDNA sequences and genome-wide nuclear data (genotyping-by-sequencing; GBS) for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…Quiroga‐Carmona & D'Elía, 2022). Geographic range size has also emerged as an important predictor of genetic variation in other taxonomic groups such as squamates (Larkin et al., 2023) and Darwin's finches (Brüniche‐Olsen et al., 2019). Interestingly, the relationship between genetic diversity and geographic range is not always straightforward, as evidenced by the case of butterflies (Mackintosh et al., 2019) and other non‐model animal species (Romiguier et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Quiroga‐Carmona & D'Elía, 2022). Geographic range size has also emerged as an important predictor of genetic variation in other taxonomic groups such as squamates (Larkin et al., 2023) and Darwin's finches (Brüniche‐Olsen et al., 2019). Interestingly, the relationship between genetic diversity and geographic range is not always straightforward, as evidenced by the case of butterflies (Mackintosh et al., 2019) and other non‐model animal species (Romiguier et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…We suspect that environmental heterogeneity within the geographic range rather than range size may have a greater influence on IBD and IBE patterns of species in the Neotropics, as has been observed in other vertebrate studies (e.g., Quiroga-Carmona and D’Elía, 2022). Geographic range size has also emerged as an important predictor of genetic variation in other taxonomic groups such as squamates (Larkin et al, 2023) and Darwin’s finches (Brüniche-Olsen et al, 2019). Interestingly, the relationship between genetic diversity and geographic range is not always straightforward, as evidenced by the case of butterflies (Mackintosh et al, 2019) and other non-model animal species (Romiguier et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we found that amphibian species inhabiting smaller ranges and higher elevations have lower intraspecific π (Figure 4c), in agreement with recent published results from De Kort et al ( 2021) who found that GD, measured as expected heterozygosity, was higher at low elevations. Geographic range size has also emerged as an important predictor of genetic variation in other taxonomic groups such as squamates (Larkin et al, 2023), pinnipeds (Peart et al, 2020), and Darwin's finches (Brüniche-Olsen et al, 2019). Interestingly, the relationship between GD and geographic range is not always straightforward, as evidenced by the case of butterflies (Mackintosh et al, 2019) and other non-model animal species (Romiguier et al, 2014).…”
Section: Discussionmentioning
confidence: 99%